Far Eastern banknote emissions of the Russian-Chinese Bank and the Russian-Asiatic Bank at the turn of the 19th and 20th centuries. The Russian, Chinese and Mongolian borderlands - Bieniaś, Juliusz; Lipinin, Joanna (Acta Archaeologica Lodziensia, 2018)
This gives an account of the activity of the Russian-Chinese Bank, later known as the Russian- Asiatic Bank, in issuing currency at the turn of the 19th and 20th centuries. It describes the Sino-Russian relationship of that period, discusses the legal basis of the issuing of currency, its range of circulation, and its exchange rate as regards Chinese currency. It demonstrates that there were significant discrepancies between the Chinese, Russian and English regulations authorizing the issuing of banknotes.